Effect of International and Indonesian Fast Foods on Plasma Ghrelin and Glucagon Like Peptide-1 (GLP-1) Levels, Hunger and Satiety Scores is Similar in Obese Adults - Handayani, D.; Oktafiani, L.D.A.; Abednego, R.T.; Andarini, S. (Pakistan Journal of Nutrition, 2016)
Background and Objective: The desire for food is regulated by appetite-associated hormones such as ghrelin and glucagon-like peptide-1 (GLP-1). Hormone release is influenced by the energy density of and macro-nutrients in food. This study assessed the effects of international and Indonesian fast food on ghrelin and GLP-1 levels, which contribute to the perception of hunger and satiety, in obese individuals. Materials and Methods: A total of 16 obese individuals were provided international fast food; after a week, the subjects were provided Indonesian fast food. Plasma samples were collected and the perceptions of hunger and satiety were assessed using a visual analogue scale before consuming time 0, 30, 60 and 120 min after consuming both kinds of fast food. Data were analyzed using unpaired t-tests, Mann-Whitney U tests, Pearson’s correlation coefficients and Spearman’s rank correlation coefficients. Results: The results revealed significant decreases in plasma ghrelin levels after 120 min of eating international and Indonesian fast foods. In contrast, plasma glucagon-like peptide-1 hormone levels did not differ significantly after consuming both kinds of fast food. The results also showed no correlation between changes in the plasma levels of ghrelin and GLP-1 and the perceptions of hunger and satiety in obese individuals. Conclusion: It is concluded that both types of fast food resulted in equal suppression of hunger and increased satiety.